ARTICULATE STORYLINE MEDIA FOR CREATIVE THINKING OF LEARNERS ON HUMAN RESPIRATORY SYSTEM MATERIAL IN ELEMENTARY SCHOOL - Daniaty SR Danial; Ghullam Hamdu; Syarip Hidayat (Jurnal Cakrawala Pendas, 2025)
This research aims to analyze the effectiveness of Articulate Storyline media on the human respiratory system material in Class V of SDN 3 Sukamenak. This study employs a qualitative approach with a Design-Based Research (DBR) method. Data collection techniques include observation, interviews, and questionnaires. The study involved 1 material expert and 1 media expert as validators, 1 classroom teacher as a respondent, and 31 fifth-grade students as participants. The results of the material expert validation showed a percentage of 94.05% in the "very valid" category, while the media expert validation obtained a percentage of 92.5%, also categorized as "very valid." The teacher's response to the media reached 84.62%, indicating a "good" category, while the students' response was 78.87%, also falling into the "good" category. These results indicate that the Articulate Storyline media on the human respiratory system is not only feasible for use as a learning tool but also has strong potential to enhance students' creative thinking skills. This media provides an interactive and engaging learning experience that supports the achievement of learning objectives more effectively.